The housing finance system in Italy and Spain: Why did a housing bubble develop in Spain - and not in Italy? - Miriam Bulbarelli (Freie Universität Berlin, Center for International Political Economy, 2016)
The international financial crisis, which started in the United States at the end of 2007, hit Europe soon afterwards. Its impact on the old continent has been enormous. A number of country-specific crises were triggered, especially in the European periphery. This essay will focus on two countries, which were affected particularly severely: Spain and Italy. In Spain, the global financial crisis was worsened by the burst of the housing bubble, which had inflated the cost of housing during the early 2000s. In Italy, in contrast, pre-existing problems with the management of high public debt, long-term stagnation in labour productivity and low government credibility made its economy vulnerable to the financial crisis. Though both countries had different experiences dealing with the global crisis, Italian and Spanish structural and economic features are largely comparable and both countries experienced an economic boom since the 2000s, especially in the housing sector. Yet, Italy did not witness a housing boom turning into a bubble and its consequences, a steep correction of housing prices - the "bust" - , whereas Spain is still recovering from it. This paper attempts to analyze the reason for this discrepancy.
urn:nbn:de:101:1-201603073690
Keywords: 330